P13.10 Club drug use, sexual behaviour and sti prevalence in sexual health clinic attendees in a uk city. (13th September 2015) - Ekong, NE; Portman, MD; Murira, J; Roche, J; Charles, P; Wilson, JD
Abstract : Introduction: Club drug (CD) use is increasing, but use in non-swinging heterosexuals and associations with sexual behaviour and STI prevalence is undocumented worldwide. Methods: Sexual health clinic attendees aged ≥16 years were invited to complete a questionnaire on sexual behaviour and drug use for two weeks per quarter in 2013–14. CD use was compared with age, sexuality, sexual behaviour and STI rates to determine any associations. Results: 2332 questionnaires were analysed; mean age 27 (16–81) years; 52% male; 75% white British; 82.6% heterosexual; 11% MSM. Lifetime CD use was 38%; 36% of these had used in the past 4 weeks (active use). CD use was higher in MSM than heterosexuals, in heterosexual males than females, and in those <25 years. Self-perceived risky sex was higher in MSM than heterosexuals using mephedrone (OR4.38 p = <0.0001), ecstasy, GHB and ketamine. MSM reported more difficulty in controlling their drug use (OR1.6, p = 0.02). Lack of condom use in the past 12 months in heterosexual CD users and non-users was the same, but CD users were more likely to have ≥3 partners (OR2.3 p = 0.0001). Heterosexual CD active users were more likely to have had anal sex in the past 4 weeks (OR2.6, p = 0.0001); recent heterosexual anal sex was associated with chlamydia (OR2.41, p = 0.0007). There were no associations between lifetime or active use of CD and STI prevalence in heterosexuals (lifetime OR0.91, p = 0.54; active OR1.02, p = 0.94) or MSM (lifetime OR1.30, p = 0.35; active OR1.21, p = 0.63). Conclusion: This is the first sexual health clinic study in the UK to assess CD use in all sexualities. Lifetime use of CD was high. CD use in heterosexuals was associated with higher risk sex but lifetime or recent CD was not associated with a higher prevalence of STIs. STI acquisition is multifactorial and is not solely determined by CD use. Disclosure of interest statement: No disclosures of interest.